Small Caribbean States and the challenge of international trade negotiations (Institute of International Relations St. AugustineTT, 1998)
Provides an insight into the FTAA negotiating process; the future of ACP/EU cooperation; the state of regional preparedness; and, the institutional requirements of these negotiations. Underscores the broader WTO framework within which these discussions must take place.
DC